Linux in a Nutshell, 4th Edition - Figgins, Stephen (O'Reilly, 2011)
Comprehensive but concise, Linux in a Nutshell is an essential desktop reference for the commands that users of Linux utilize every day. It covers all substantial user, programming, administration, and networking commands for the most common Linux distributions. It's several quick references rolled into one: sed, gawk, RCS, CVS, vi, Emacs, bash, tcsh, regular expressions, package management, bootloaders, and desktop environments are all covered in this clear, to-the-point volume, along with core command-line utilities.